A comparative study on the effect of Ranolazine and Ivabradine on high sensitivity C-reactive protein in cardiac patients - Mathew George; Lincy Joseph; Leena P N; Betty Mary Mathew; Dany Sebastian; Sony Mariam Saji (International Journal of Pharmacy and Analytical Research, 2022)
C-reactive protein (CRP) is a substance produced by the liver in response to inflammation. High CRP levels can indicate that there is inflammation in the arteries of the heart, which can mean a higher risk for heart attack. Ranolazine and Ivabradine are used in the treatment of cardiac problems such as angina, heart failure and in patients with acute coronary syndrome. These drugs have found to have action on C-reactive protein, which is a pentameric protein found in blood plasma whose levels rise in response to inflammation. Increased CRP levels indicate risk for atherosclerotic diseases. The aim of the study was to compare the effect of Ranolazine and Ivabradine on high sensitivity C - reactive protein in cardiac patients. Method: This was a prospective studyconducted in the Department of Cardiology, Pushpagiri Medical College Hospital, Thiruvalla. All patients willing to participate were explained about the brief study procedure. 60 patients were taken for the study. The patients were selected based on the inclusion and exclusion criteria. Residual blood was collected at the time of admission and after 2 weeks. The hsCRP levels was analyzed by using semi auto-analyzer. The results obtained from the study can be compared with the normal range of hsCRP levels. The effectiveness of Ivabradine and Ranolazine on hs-CRP levels reported that both the drugs decreased the hs-CRP levels. Ivabradine decreased hs-CRP levels more efficiently than Ranolazine.